PENGARUH SCALE TERHADAP PRODUKTIVITAS PADA SUMUR BN-52, BN-104, DAN BN-110 DI LAPANGAN “X” - Abhikama Pradipta; Lestari Lestari; Samsol Samsol (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2019)
BN-52, BN-104, and BN-110 wells are located on the X field, PT. PERTAMINA FIELD RAMBA ASSET 1, South Sumatra. The three wells are oil-producing wells in field X. Using the Vogel equation, the IPR curve and maximum flow rate of each well are obtained, which are 152.14 BOPD, 57.2 BOPD, and 53.76 BOPD respectively. By using the exponential Decline Curve Analysis calculation method, it can be seen the rate of decline in production, as well as the time of well production to economic limit. The results of the Decline Curve Analysis show that the BN-52 well will still be in production until March 2022, and the BN-110 well can produce until March 2020. In the analysis with the Stiff & Davis Method, carbonate deposits are proven, with each Stability Index value +1.19, +1.60, and +1.35, whereas with the Skillman, Mcdonald & Stiff method there was no scale sulfate, with S values of each well at 57,272 meq / l, 54,416 meq / l, and 55,147 meq / l. The scale causes oil production to decrease, consequently the IPR curve shifts to the left. The decreasing production of the three wells is due to a scale that inhibits the flow rate. Maximum flow rate was obtained by using the Standing correlation in each well of 100.06 BOPD, 54.53 BOPD, and 28.72 BOPD. The decline in oil production caused by scales must be handled appropriately.